The practice of English language teaching / Jeremy Harmer - Harmer, Jeremy
The highly acclaimed Practice of English Language Teaching is the essential guide for teachers of English in a wide range of contexts. The fifth edition has been revised to reflect new developments in language teaching. It explains current pedagogy to teachers who want to access the most relevant ELT practices and incorporate them into their lessons.